In ovo nano-silver and nutrient supplementation improves immunity and resistance against Newcastle disease virus challenge in broiler chickens - Bhanja, Subrat Kumar; Rath, Pradeepta Kumar; Goel, Akshat; Mehra, Manish; Dhara, Sujoy K.; Paswan, Vinod K.; Attia, Youssef A.; Alqhtani, Abdulmohsen Hussen; Ali, Ahmed B. A.; Shehata, Abdelrazeq M. (Frontiers in Veterinary Science, 2022)
Silver nanoparticles (AgNPs) interact with the microbes and host immune system to protect against diseases. Fertile broiler eggs (n = 900) were allotted to six groups: un-injected control, sham (sterile water), AgNPs (50 μg), AgNPs+Amino acids (Methionine-10 mg + Arginine-25 mg), AgNPs+Vitamins (Vit B1-72μg + Vit B6-140μg), and AgNPs+Trace Elements (Zn-80 μg and Se-0.3 μg) and incubated for 18 days. On 18th embryonic day, 0.6 ml test solution was injected at the broad end of egg using 25 mm needle and transferred to hatcher. Post-hatch, half of the chicks from each group were vaccinated with Newcastle disease (ND) vaccine, and the other half were kept as unvaccinated unit and reared for 42 d with standard management practices. Hatchability, 1st and 42nd d body weight, feed intake, and feed conversion ratio were similar between treatment groups in both vaccinated and unvaccinated units. The relative weight of bursa Fabricius and thymus was similar, but spleen weight was higher (P ≤ 0.05) in AgNPs, AgNPs+Vits, and AgNPs+TEs chicks than control group. Cellular immune response (against mitogen phytohemagglutinin-P) was higher (P ≤ 0.05) in AgNPs+TEs chicks, whereas HA titer against sheep red blood cells antigen, serum IgG, IgM, and HI titer against ND vaccine was apparently higher in AgNPs+Vits group chicks than control. No clinical symptoms were observed in the vaccinated groups except for a few control birds 6 days postchallenge (PC). Three days PC, unvaccinated birds show depression, off feed, greenish diarrhea, and nasal discharge and the control group started dying. The highest cumulative infection (CI) was observed in sham (79.17%) and un-injected control (75%), but lowest in AgNPs+AAs birds (58.33%) on 3rd dpi. The CI reached 100% on 5th dpi in control groups and AgNPs, and 91.67% and 93.75% in AgNPs+TEs and AgNPs+AAs group, respectively. The AgNPs+TEs and AgNPs+AAs group birds lived for more than 90 h compared to 75 h in control groups and also had higher IL-6 and IL-2 gene expressions at 24 h PC. It was concluded that 50 μg/egg AgNPs with vitamins (B1 and B6) and trace elements (Zn and Se) improved performance, but AgNPs with trace elements and amino acids enhanced immune response and resistance against vND virus challenge in broilers.